Thoughts on the Aesthetics of Malay Artifacts - Zakaria Ali (Wacana Seni Journal of Arts Discourse, 2006)
Artitacts are old things, often kept in the museums, cataloged, analyzed, debated, regularly served to illustrate the impact or styles in art history treatises. and promote divergent viewpoints in archeological reports. George Kubler insists that artifacts and works of arts are included in the history of things, ia which a series of replicas and unique examples, both tools and expressions create a shape of time, from which a collective identity of a tribe, class, or nation emerges. ''This self-image reflected in things is a guide and a point of reference to the group for the future, and it eventually becomes the portrait given to posterity" (Kubler 1976: 9).